Analysis Of Compensation And Work Climate On Teacher Performance Through Work Motivation At SMK Negeri 1 Percut Sei Tuan - Fahrul Lubis; Hernawaty Hernawaty; Erwansyah Erwansyah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of compensation and work climate on teacher performance through work motivation as an intervening variable at SMK Negeri 1 Percut Sei Tuan. This study uses a quantitative approach with a survey method. The research population consists of all teachers and employees of SMK Negeri 1 Percut Sei Tuan, totaling 119 people, who also serve as the research sample (population research). Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of the SmartPLS application. The results showed that compensation and work climate had a positive and significant effect on teacher performance. In addition, compensation and work climate also had a positive and significant effect on work motivation. Work motivation was proven to have a positive and significant effect on teacher performance. The results of the indirect effect test showed that work motivation was able to significantly mediate the effect of compensation and work climate on teacher performance. The coefficient of determination value showed that compensation and work climate were able to explain 38.3% of the variation in work motivation, while compensation, work climate, and work motivation together were able to explain 56.3% of the variation in teacher performance. The conclusion of this study confirms that improving teacher performance can be achieved through fair compensation management, the creation of a conducive work climate, and the strengthening of teacher work motivation. These findings are expected to serve as a basis for schools in formulating strategic policies to improve teacher performance and professionalism in the vocational education environment.